Mutation in Wzz(fepE) Linked to Altered O-Antigen Biosynthesis and Attenuated Virulence in Rough Salmonella Infantis Variant - Nneka Vivian Iduu; Steven Kitchens; Stuart B. Price; Chengming Wang (Veterinary Sciences)
Salmonella enterica serovar Infantis has emerged as a prevalent foodborne pathogen in poultry with significant global health implications. This study investigates the molecular characteristics influencing virulence in a S. Infantis rough variant collected from a poultry farm in the USA. In this study, whole genome sequencing and comparative genomics were performed on smooth and rough poultry S. Infantis isolates, while chicken embryo lethality assay was conducted to assess their virulence. Comparative genomics between isolates was analyzed using Mauve pairwise Locally Collinear Blocks to measure the genetic conservation. Embryo survival rates between the isolates were compared using the Kaplan–Meier curves. High genomic conservation was observed between the two isolates, but a frameshift mutation was detected in the Wzz(fepE) gene of the rough variant, resulting in early protein truncation. The chicken embryo lethality assay showed that the lethality rate of the smooth strain was higher than that of the rough strain (p < 0.05). This study identifies a frameshift mutation in the Wzz(fepE) gene, leading to protein truncation, which may reduce bacterial virulence by impacting O-antigen biosynthesis in the rough Salmonella Infantis variant. These findings deepen our understanding of S. Infantis pathogenesis and suggest that targeting the Wzz(fepE) gene or related pathways could be a promising strategy for developing effective vaccines and therapeutic interventions.